AN ERROR ANALYSIS IN PAPER PRESENTATIONS: A CASE STUDY OF INDONESIAN EFL LEARNERS - Merizawati, Heny (Linguists : Journal of Linguistics and Language Teaching, 2018)
This paper examines errors in paper presentations of Indonesian EFL learners. It aims to identify the types of errors and the most often errors committed by 124 sophomores of the class of 2016 in State Islamic Institute of Bengkulu (IAIN Bengkulu). The researcher used qualitative approach with descriptive analysis. The data were collected from recorded paper presentations from the Semantics-Pragmatic course and a questionnaire sheet. The researcher found 17 types of errors from paper presentations which were omission(20.27%) followed by Subject-Verb Agreement (SVA) (12.10%), plural form (11.09%), tense (8.82%), addition (7.81%), wrong Parts of Speech (PoS) (7.63%), fragment (7.15%), redundancy (5.30%), possessive noun (5.24%), wrong choice of word (3.87%), preposition (2.56%), articles(2.56%), disordering (2.20%), singular form (1.72%), misinformation (0.71%), parallel structure (0.53%), and negative form (0.35%). Meanwhile, from the questionnaire sheet, it shows that the incorrect use of tenses was the most often errors that learners thought they committed and it was the most difficult one learners assumed. As a result, the five biggest errors occurred went to omission, SVA, plural form, tense and addition. It seems that interlingual or transfer errors as well as intralingual and developmental errors influence learners to commit the errors.